Study of Administrative, Pharmaceutical, and Clinical Aspects of Hypertension Patient Prescriptions at Advent Hospital, Medan - Saragih, Maria Lady; Simanjuntak, Nerly Juli Pranita; Novriani, Erida (PCJN: Pharmaceutical and Clinical Journal of Nusantara, 2025)
Hypertension is a common chronic disease requiring precise pharmacological management to prevent complications. Inappropriate prescriptions may lead to treatment failure or adverse events. This study aimed to evaluate the completeness of prescriptions for hypertensive outpatients at Advent Hospital Medan based on administrative, pharmaceutical, and clinical aspects. This descriptive retrospective study analyzed 303 prescriptions collected from January to March 2024. Evaluation criteria included patient and prescriber identity, dosage form, drug strength, usage instructions, indication accuracy, dosage accuracy, and potential drug interactions. Results showed administrative completeness was high, with 100% inclusion of most identity elements, but 0% for weight and height. Pharmaceutical completeness was suboptimal, with only 25.08% including dosage form. Clinically, all prescriptions were appropriate in terms of indication, dose, and timing, and showed no duplication. However, 88.11% of prescriptions contained potential drug interactions, with 68 major interactions identified. The most frequent were Amlodipine–Simvastatin and Spironolactone–Candesartan combinations. These findings indicate that while clinical accuracy was excellent, pharmaceutical documentation and interaction screening need improvement. Collaboration between prescribers and pharmacists is essential to enhance medication safety.